2009
DOI: 10.1016/j.physc.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen reduction on the structural and electronic properties of electron-doped Sr1−xLaxCuO2 thin films

Abstract: Single phase, c-axis oriented, e-doped, Sr 1-x La x CuO 2 thin films were epitaxially grown on KTaO 3 and DyScO 3 substrates by reactive rf sputtering. As-grown films being insulating due to oxygen excess, oxygen reduction is necessary to observe superconductivity. Two different procedures were employed to reach superconductivity.On one hand an in-situ reduction process was conducted on a series of films deposited on both types of substrates. On the other hand, an ex-situ reduction procedure was performed sequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 18 publications
(27 reference statements)
3
40
0
Order By: Relevance
“…12 (b). In accordance with literature 27,48 we found that the c-axis decreases and the a-axis increases monotonically during reduction. Furthermore, we found that the unit cell volume V increases as well (cf.…”
Section: Vacuum Annealing Timesupporting
confidence: 93%
See 3 more Smart Citations
“…12 (b). In accordance with literature 27,48 we found that the c-axis decreases and the a-axis increases monotonically during reduction. Furthermore, we found that the unit cell volume V increases as well (cf.…”
Section: Vacuum Annealing Timesupporting
confidence: 93%
“…As excess oxygen forms O 2− ions on interstitial sites, it traps free charge carriers from the CuO 2 planes, which increases the resistivity and suppresses superconductivity. Therefore, ρ 300K decreases and T c increases with the removal of excess oxygen, as reported before 27,48 . We further observed the reduction process by analyzing the evolution of the lattice constants with proceeding t a , as displayed in Fig.…”
Section: Vacuum Annealing Timesupporting
confidence: 72%
See 2 more Smart Citations
“…IL cuprates are particularly interesting because of their crystallographic structure: the simplest among layered cuprates. On the other hand, the IL compounds are metastable and single crystal can be stabilized only in thin film form [23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%